Malaysian case studies on the relation between the use of green space and health promotion - Abdul Aziz, Nor Akmar; Konijnendijk, C. C.; Stigsdotter, U. K.; Nillson, Kjell (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
This study explores the use of green spaces and visitors´ self-reported health for five parks located in Kuala Lumpur and Kuching, Malaysia. A survey was conducted among the residents living within two kilometres radius from the park boundaries. A total of 1692 respondents participated in the survey. The results indicate differences in self-reported health between people according to frequency of park use, apart from the differences explained by the sociodemographic factors. The results related to the differences in self-reported health according to the distance of the residence from the park were not statistically significant. Among the ‘health improving’ recommendations made to close friends and family members were going for a vacation and engaging in some exercise or sport activities. These were ranked higher than taking a break in a quiet and peaceful park or forest. Although this study offers some further evidence of the positive impacts of using green spaces on health, the results show some new findings as compared to similar studies conducted in Europe. Thus, more in-depth works are needed in order to provide information to Malaysian decision makers and green space managers